WHEN COPD ISN’T COPD: A FOURTEEN-YEAR CASE STUDY OF ADULT-ONSET SWYER-JAMES-MACLEOD SYNDROME - Małgorzata Dworniczak,; Maria Kaniecka,; Anna Karcz,; Barbara Pająk,; Oliwia Wróblewska,; Sofiya Salash,; Aleksandra Romaniuk,; Jakub Majewski,; Hubert Bołdys-Żegocki,; Artur Koza, (International Journal of Innovative Technologies in Social Science, 2025)
Swyer-James-MacLeod (SJML) syndrome, also known as unilateral hyperlucent lung syndrome, is a rare post-infectious pulmonary disorder characterized by emphysematous changes, unilateral pulmonary artery hypoplasia, and regional hypoperfusion [1, 2]. The hallmark radiographic feature - often referred to as the “hyperlucent lung” or “clear lung sign” - reflects air trapping with decreased vascular markings and serves as the signature diagnostic clue of this condition [3, 6]. SJML syndrome typically develops following childhood bronchiolitis or pneumonitis but may remain unrecognized until adulthood due to its nonspecific respiratory presentation [4, 7].We report the case of a 41-year-old woman who has been under observation and treatment for the past 14 years. Despite chronic, non-productive cough and persistent unilateral pulmonary abnormalities, she was not initially diagnosed with SJML syndrome due to the absence of standardized diagnostic criteria. Radiological assessment, including high-resolution computed tomography (HRCT) and CT angiography, revealed a hyperlucent and volume-reduced left lung with bronchiectasic changes and pulmonary arterial hypoplasia, findings consistent with described syndrome. Pulmonary function tests demonstrated moderate airflow obstruction, while the patient’s prolonged childhood exposure to tobacco smoke may have contributed to airway remodeling.This long-term follow-up highlights the diagnostic importance of recognizing unilateral hyperlucency as the signature sign of SJML syndrome and underscores the need for multidisciplinary monitoring to optimize long-term respiratory outcomes [5–7].